A new record of the genus Hueikaeana (Tettigoniidae: Phaneropterinae) and a new species from China - Wang, Gang; Zhou, Xu-Ling; Shi, Fu-Ming (Zootaxa, 2010)
The genus Hueikaeana Ingrisch, 1998 is reported for the first time from China with the species, H. alia Gorochov, 2004 and a new species, H. albopunctata Wang & Shi, sp. nov.. The diagnostic characters are described and figured. A key to the known species is provided. All specimens (including type specimens) are deposited in the Museum of Hebei University.